Multi‐Nonvolatile State Resistive Switching Arising from Ferroelectricity and Oxygen Vacancy Migration. Issue 24 (25th April 2017) - Lü, Weiming; Li, Changjian; Zheng, Limei; Xiao, Juanxiu; Lin, Weinan; Li, Qiang; Wang, Xiao Renshaw; Huang, Zhen; Zeng, Shengwei; Han, Kun; Zhou, Wenxiong; Zeng, Kaiyang; et al.
Abstract : Resistive switching phenomena form the basis of competing memory technologies. Among them, resistive switching, originating from oxygen vacancy migration (OVM), and ferroelectric switching offer two promising approaches. OVM in oxide films/heterostructures can exhibit high/low resistive state via conducting filament forming/deforming, while the resistive switching of ferroelectric tunnel junctions (FTJs) arises from barrier height or width variation while ferroelectric polarization reverses between asymmetric electrodes. Here the authors demonstrate a coexistence of OVM and ferroelectric induced resistive switching in a BaTiO3 FTJ by comparing BaTiO3 with SrTiO3 based tunnel junctions. This coexistence results in two distinguishable loops with multi‐nonvolatile resistive states. The primary loop originates from the ferroelectric switching. The second loop emerges at a voltage close to the SrTiO3 switching voltage, showing OVM being its origin. BaTiO3 based devices with controlled oxygen vacancies enable us to combine the benefits of both OVM and ferroelectric tunneling to produce multistate nonvolatile memory devices. Abstract : The coexistence of oxygen‐vacancy migration and ferroelectric‐induced resistive switching in BaTiO3 ferroelectric tunnel junctions through several sets of comparison between BaTiO3 ‐ and SrTiO3 ‐ based tunnel junctions is described. This coexistence results in two distinguishable loops with multi‐nonvolatile resistive states in a single device, showing that controlling oxygen vacancies is an effective way to produce multistate memory devices.